Institutional and innovative transformations of sectors of the national economy under the influence of digitalization - Chornodid, Ihor; Novak, Yevheniia (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the study of institutional and innovative transformations of sectors of the national economy under the influence of digitalization, which is becoming a key factor in the modernization of production and management systems. The paper substantiates that digital technologies not only change technical processes, but also cause deep institutional disruptions, transforming rules, standards and forms of interaction between economic agents. Based on the analysis of the aerospace complex and the construction sector, it is shown that digitalization performs a dual function: it acts as a tool for increasing production efficiency and at the same time a catalyst for reviewing regulatory and coordination mechanisms. In the aerospace industry, the digitalization of certification processes, the introduction of digital twins and the product lifecycle management (PLM) system contribute to reducing R&D costs, increasing safety and international integration. At the same time, they increase the requirements for the protection of intellectual property, cybersecurity and the consistency of international standards. In the construction sector, digital transformation is associated with the spread of BIM modeling, blockchain solutions and digital twin technologies, which provide a reduction in design and construction times, increased transparency and energy efficiency. At the same time, institutional challenges are becoming more relevant, associated with the low level of digital competences of personnel, the high cost of technologies for SMEs and ensuring the formation of unified electronic standards. The article emphasizes that the key result of digitalization is the transformation of product certification into a continuous integrated process that accompanies the entire life cycle of a product or object. This requires a review of the role of regulatory authorities, the creation of innovation clusters and the development of intermediary institutions capable of ensuring the harmonization of standards and supporting adaptation to new market conditions. It is proposed that the success of institutional and innovative transformations depends on the combination of technological solutions with new models of management and cooperation, which opens up prospects for the integration of sectors into global value chains.